Developing thematic-integrated module based on guided discovery to improve critical thinking and student science attitude - Ningrum Perwitasari; Djukri Djukri (Jurnal Prima Edukasia, 2018)
This research aimed (1) to produce thematic-integrated module based on a guided-discovery to improve critical thinking and scientific attitude of grade IV students of SDN Margoyasan, and (2) to know the effectiveness of the developed learning module. The research was Research and development of Borg and Gall model which consisted of ten steps. The data were collected by interview, product evaluation, questionnaires, observation, and examination. The data were analyzed by using paired sample t-test and independent sample t-test with significant level of 0.05. The research result were (1) thematic-integrated module based on a guided-discovery. The product feasibility that was assessed based on material expert, media expert, teacher’s and student’s responses was very feasible. (2) The results of field trial test showed that the developed thematic-integrated module based on a guided-discovery was effective to improve the student’s critical thinking and scientific attitude, and it was based on the operational field trial test which obtained p0.05, means that there are significant differences on students who were taught by using the developed learning module compare to student who were not taught by using the developed learning module.